Worlds in a Museum : Exploring Contemporary Museology (Book collections on Project MUSE., 2020)
Held on the occasion of Louvre Abu Dhabi?s first anniversary, the symposium 'Worlds in a Museum' addressed the topic of museums in the era of globalisation, exploring contemporary museology and the preservation and presentation of culture within the context of changing societies. Departing from the historical museum structure inherited from the Enlightenment, leading experts from art, cultural, and academic institutions explore present-day achievements and challenges in the study, display and interpretation of art, history, and artefacts. How are ?global? and ?local? objects and narratives balanced - particularly in consideration of diverse audiences? How do we foster perspective and multiculturalism while addressing politicised notions of centre and periphery? As they abandon classical canons and categories, how are museums and cultural entities redefining themselves beyond predefined concepts of geography and history?0This collection of essays arises from the symposium 'Worlds in a Museum' organised by Louvre Abu Dhabi and École du Louvre.